Manajemen Strategi dan Kinerja Keuangan Untuk Mencapai Stabilitas PT Hanjaya Mandala Sampoerna Tbk Tahun 2021-2023 - Zai, Rahmat Christ Notatema (Asosiasi Dosen Akuntansi Indonesia, 2024)
This study aims to analyze the effect of strategic management and financial performance on the stability of PT Hanjaya Mandala Sampoerna Tbk (Sampoerna) in facing increasingly fierce competition in the cigarette industry in 2021-2023. Sampoerna's strategic management focuses on product innovation, diversification, and distribution optimization, while financial performance is evaluated through various financial ratios such as liquidity, solvency, and profitability. The research method used is the quantitative method. The data for this study were obtained from the company's annual financial statements and sustainability reports for the 2021-2023 period. The results of the analysis show that the diversification strategy of smoke-free products and technological innovations such as IQOS and HEETS, as well as solid financial management, contribute significantly to the stability of the company. Financial ratios show that Sampoerna is able to maintain good liquidity, solvency, and profitability despite facing various external challenges such as excise tax increases and regulatory changes.